What Adaptation Stories are UK Newspapers Telling? A Narrative Analysis. Issue 8 (16th November 2020) - Harcourt, Rachel; Bruine de Bruin, Wändi; Dessai, Suraje; Taylor, Andrea
ABSTRACT: Media coverage of climate change impacts and adaptation will likely influence how citizens think society can and should adapt. Here, we undertook the first analysis of UK newspaper adaptation coverage. We identified five prominent adaptation narratives: (1) the government should build more flood defences, (2) home owners should buy flood insurance, (3) individuals should become more informed, (4) the farming industry should innovate, (5) and the natural environment should fight for its survival. We find that only some of the more immediate climate change impacts likely to affect the UK are presented as necessitating a response. The government is considered primarily responsible while UK citizens are given few and narrow responsibilities. The range of adaptive actions under consideration is limited and unchallenging to the status quo. In summary, newspaper coverage presents a restricted view as to when the UK should adapt and how it could adapt.